ON THE PHOTOMETRY OF CC ANDROMEDAE - Udovichenko, S. N. (Одеські астрономічні публікації, 2017)
The photometric observation of δ Scuti star CC Andromedae using the 48 cm telescope with CCD photometer and the V filter of the UBV system at the Astronomical Observatory of Odessa National University have been made. The calculations of the time series data by using a new program Period04 (Lenz and Breger,2004) for multiple-frequency analysis, a seven-frequency solution has been developed. Also, the new frequency analyses for observation CC Andromedae made by Fitch in 1956 and 1957 have a seven-frequency solution, although Fitch (1967) give a six-frequency solution. The new frequency values closely fits all data of observations. The mode identification shows, that most frequencies correspond to radial and nonradial modes.